Assessment of knowledge, perceptions, and readiness of healthcare professionals towards clinical pharmacogenomics implementation in Qatar: a mixed-method study - Shaikha Jabor Alnaimi; Fatima Ajaj; Ahmed Awaisu; Turfa Alhathal; Shaban Mohammed; Moza Alhail (Taylor & Francis Group, 2024)
Introduction Pharmacogenomics implementation in clinical practice is anticipated to improve our understanding of individual variations in drug response and optimise the safety and efficacy of drug therapy. We aimed to assess the knowledge, perceptions, and readiness of physicians, pharmacists, and nurses in Qatar regarding the implementation of clinical pharmacogenomics.Methods A mixed-method study with an explanatory sequential design was conducted. Phase I was the quantitative phase which involved sending an online survey to physicians, pharmacists, and nurses. Phase II was the qualitative phase which involved conducting focus group discussions.Results A total of 802 responses were collected, with a response rate of 20%. Only 15.4% of participants had previous pharmacogenomics-related training. The median knowledge score for healthcare professionals was 4 out of 10 denoting low level of knowledge. However, compared to other professions, pharmacists had a higher knowledge score (p-value <0.001) and Doctor of Pharmacy (PharmD) holders scored higher than BSc holders (p-value <0.001). Despite the low level of knowledge, perceptions of healthcare professionals were positive. In addition, the majority believed knowledge of pharmacogenomics is necessary and that counselling patients on pharmacogenomics requires specialised training pharmacogenomic principles in practice. The main themes extracted from the focus group discussions were knowledge, outcome expectations, preparedness, facilitators, barriers, public education, and implementation planning. Regarding readiness, most healthcare professionals reported that they are not currently confident in applyingConclusions Healthcare providers have a low level of knowledge of pharmacogenomics. Despite this, the majority have positive perceptions towards its implementation in practice. Compared to other professionals, pharmacists with a PharmD degree scored higher in the knowledge assessment. Most healthcare providers report low confidence regarding the readiness for the implementation of pharmacogenomics and report a lack of knowledge, specialised training, and clinical guidelines as barriers.